Butterworth low-pass filter design / Ismahalili Ishak - Ishak, Ismahalili (2009)
This work highlighted on the development carried out on miniaturized radio frequency (RF) low-pass filter. The design, simulation and fabrication of Butterworth low-pass filter (BPLF) was accomplished using Rogers Duroid substrate for low-k substrate. Design, simulation and analysis of Butterworth low-pass filter using high-k substrate was also carried out. It was observed that, the use of high-k resulted in miniaturization of Butterworth low-pass filter.